Characterization of Netupitant Degradation Products Employing LC-QTOF-MS and Computational Tools - Mahajan, Bhavna; Miniyar, Pankaj; Chodankar, Rahul; Mahajan, Anand; Mahajan, Moreshwar (Asian Journal of Chemistry, 2026)
The present study evaluates the stability of netupitant under various environmental stress conditions and identifies the degradation products formed during the degradation process. In addition, the study predicts the pharmacokinetic and toxicological properties of these degradation products using advanced analytical and computational approaches. Isocratic liquid chromatography was used to separate stress samples, high-resolution quadrupole time-of-flight mass spectrometry was used to elucidate the structure of these samples. Computational platforms were used in making predictions of toxicity and molecular docking simulations were performed to assess the relative binding affinities of the parent drug and its degradants to the human neurokinin-1 receptor. Netupitant was susceptible to oxidative and hydrolytic stress, mainly through oxidative cleavage of the piperazine ring. Molecular docking showed that netupitant has the best neurokinin-1 receptor binding affinity (-12.1 kcal/mol) and structural loss in the degradants slightly alters the binding affinity towards the receptor (between -11.3 and -10.2 kcal/mol). Shifting the degradation products through software screens comprising the pkCSM webserver, ToxTree and OSIRIS property explorer yielded predictions for various pharmacokinetic and toxicity-related parameters. The computational predictions highlighted high intestinal absorption and hepatotoxicity across all compounds, with specific mutagenic structural alerts identified in one degradation product and a tumorigenic alert in another.